Asupan Makan, Status Gizi dan Penanda Inflamasi pada Penyakit Ginjal Kronik dengan Terapi Hemodialisis: Asupan Makan, Status Gizi dan Penanda Inflamasi pada Penyakit Ginjal Kronik dengan Terapi Hemodialisis - Isnawati, Muflihah; Larasati, Meirina Dwi; Hendriyani, Heni (Universitas Airlangga, 2026)
Background: Hemodialysis therapy in patients with chronic kidney disease carries a high risk of malnutrition and chronic inflammation, contributing to poor clinical outcomes. Dietary intake is a key consideration in nutritional management, yet its relationship with nutritional status and inflammation remains inconsistent. Objectives: This study examined the relationship between dietary intake, nutritional assessment, and inflammatory markers in chronic kidney disease patients undergoing hemodialysis. Methods: This study employs a cross-sectional design, involving 80 adult patients on maintenance hemodialysis. Data on macronutrient and micronutrient intake were obtained using a 24-hour dietary recall method. Nutritional assessment was evaluated using body fat percentage, mid-upper arm circumference, serum albumin and the Malnutrition Inflammation Score. Inflammatory profile was assessed using hs-CRP and TIBC. Spearman correlation and multivariate linear regression analyses was applied. Results: Energy and protein intake per kilogram of body weight were inversely correlated with body fat percentage (r=−0.379 and −0.417, respectively; p-value<0.01) and MUAC (r=−0.270 and −0.338; p-value<0.05). Multivariate analyses showed that dietary intake, age and dialysis duration were not independent predictors of serum albumin or MIS. However, regression models for body fat percentage and MUAC were significant (p-value<0.05), explaining 17% of the variance. No statistically significant associations were observed between dietary intake and inflammatory profiles. Conclusions: Dietary intake contributes to variations in body composition but is not an independent determinant of biochemical or inflammatory indicators. Nutritional and inflammatory status in hemodialysis patients is multifactorial, highlighting the need for comprehensive nutritional assessment.